The primal connection - Sisson, Mark, 1953- (Primal Nutrition, 2013)
A follow-up to the best-selling The Primal Blueprint draws on the author's evolutionary research to explore genetic reasons behind why people feel depressed and unfulfilled in spite of positive outward circumstances, outlining simple lifestyle strategies for promoting personal contentment.